Novel model artificial intelligence doctor assistant for intelligent medical support - Sеlvaraj S.; Rajaprakash, S.; K, Shantha Shalini; Mariappan, R. (Edelweiss Applied Science and Technology, 2025)
Artificial intelligence (AI) has revolutionized various industries, and healthcare is no exception. In this research article, we explore the concept of an AI doctor assistant—a novel approach to enhance healthcare delivery through intelligent medical support. We discuss the potential benefits, challenges, and ethical considerations associated with implementing AI doctor assistants. The paper presents an overview of AI techniques employed in medical diagnosis, patient monitoring, treatment planning, and medical research. Furthermore, we review existing AI-based doctor assistant systems, highlighting their capabilities and limitations. We discuss the importance of data privacy, patient confidentiality, and regulatory compliance in designing and deploying AI doctor assistants. By analyzing current research, addressing challenges, and outlining future directions, this paper aims to contribute to the ongoing development and adoption of AI-driven technologies in the healthcare domain.